Interdisciplinary examinations carried out on heterogeneous coarse ceramics from Neolithic lakeside settlements in the Northern Alpine Foreland (3900–3500 BCE): Analysis strategy and preliminary results from a test series using pXRF. (June 2019) - Stapfer, Regine; Heitz, Caroline; Hinz, Martin; Hafner, Albert
Abstract: In recent decades numerous Neolithic lakeside and wetland settlements have been investigated in Switzerland, southern Germany and eastern France. The finds from these settlements indicate that complex relationships and close contacts existed between the inhabitants of different settlements and regions. This can be seen in ceramic vessels that exhibit similarities to those from other regions based on their style, manufacturing technique and raw materials. Although the use of chemical and archaeometric analyses to determine the origin of pottery has been well established for years and despite promising investigations, such analyses have hardly ever been carried out in the study region; as a result, the topic of mobility has rarely been examined. In order to better understand mobility patterns in Neolithic societies by combining stylistic analyses with a chemical characterisation of the potter's clay used, this paper explores the use of portable energy dispersive X-ray fluorescence (pXRF) analysis as a means of chemically characterising ceramics. Since studies on the use of pXRF to examine handmade, heterogeneous and coarsely tempered ceramics are rare, it seems necessary to evaluate the method. This paper presents the development of a strategy for the analysis of large series of handmade coarse ceramics from prehistoric settlements. Two examples illustrate the possibilities of and limitations to pXRF analysis on pottery for the detection of mobility patterns of Neolithic societies in the Northern Alpine Foreland.